Grapevine leaf physiology and morphological characteristics to elevated CO2 in the VineyardFACE (Free air Carbon dioxide Enrichment) experiment - Wohlfahrt, Yvette; Krüger, Katja; Papsdorf, Daniel; Tittmann, Susanne; Stoll, Manfred (Frontiers in Plant Science, 2022)
Atmospheric carbon dioxide (CO2) concentration has continuously increased since pre-industrial times and has currently reached an average growth rate of 2.3 ppm per year. For the majority of plant species elevated CO2 (eCO2) improves photosynthesis and thus plant biomass production. To investigate the effects of eCO2 on leaf physiology and morphological leaf characteristics the two Vitis vinifera L. cultivars, Riesling and Cabernet Sauvignon, grown in the VineyardFACE (Free Air Carbon dioxide Enrichment) system were used. The VineyardFACE is located at Geisenheim, Rheingau comparing future atmospheric CO2-concentrations (eCO2, predicted for the mid-21st century) with current ambient CO2-conditions (aCO2). Experiments were operated under rain-fed conditions for two consecutive years (2015 and 2016). For both varieties and CO2 treatments leaf gas exchange measurements were performed as well as measures of epidermal flavonoid (Flav) and leaf chlorophyll (Chl) indices by using a portable leaf clip. Furthermore, leaves were sampled for spectrophotometric analysis of the leaf pigments chlorophyll a (Chl a), chlorophyll b (Chl b) and carotenoid (Car). Additionally, leaf cross-sections were produced as permanent preparations to investigate morphological characteristics of the leaf structure. Pictures were taken using a light microscope and consecutive measurements were conducted with an open source image software. Both cultivars did not differ in leaf chlorophyll meter readings or leaf pigments between the two CO2 treatments while net assimilation was highly stimulated for both seasons. Differences found in leaf cross-sections were detected in palisade parenchyma and epidermal thickness of Cabernet Sauvignon under eCO2, whereas Riesling remained unaffected in morphological characteristics. The observed results within grapevine leaf tissues provide insights to seasonal adaptation strategies of grapevines under elevated CO2 concentrations predicted in future.